2021
DOI: 10.1177/0363546520980431
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Activity Levels Correlate With Early Cartilage Degeneration After Anterior Cruciate Ligament Reconstruction

Abstract: Background: The association between activity level after anterior cruciate ligament (ACL) reconstruction (ACLR) and development of posttraumatic osteoarthritis (PTOA) remains unclear. This study investigated the relationship of patient-reported outcomes and progressive cartilage degenerative changes at 3 years after ACLR. Hypothesis: Higher activity levels, as measured by Marx scores, are significantly correlated with early cartilage degeneration after ACLR. Study Design: Cohort study; Level of evidence, 2. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Overall daily walking, measured with daily steps, and exercise intensity, measured with time spent in MVPA, should be monitored as individuals rehabilitate after ACLR. In agreement with our results, Friedman et al (24) found higher patient-reported activity levels (Marx activity scores) associated with greater T1rho cartilage compositional degeneration 3 yr after ACLR. Because of the cross-sectional nature of our study, it remains unknown how time spent in MVPA changes throughout ACLR rehabilitation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall daily walking, measured with daily steps, and exercise intensity, measured with time spent in MVPA, should be monitored as individuals rehabilitate after ACLR. In agreement with our results, Friedman et al (24) found higher patient-reported activity levels (Marx activity scores) associated with greater T1rho cartilage compositional degeneration 3 yr after ACLR. Because of the cross-sectional nature of our study, it remains unknown how time spent in MVPA changes throughout ACLR rehabilitation.…”
Section: Discussionsupporting
confidence: 93%
“…T1rho MRI relaxation times are influenced by joint loading, undergoing transient increases during unloading (22) and decreasing throughout the day due to loading during daily activities (23). Recent literature suggests that higher patient-reported physical activity levels associate with lesser proteoglycan density after ACLR, indicating that higher physical activity levels may be detrimental to cartilage health (24). However, self-reported measures of physical activity are known to overestimate true physical activity levels compared with objective measures (25), and we hypothesize that evaluating objective physical activity outcomes rather than self-reported may yield different results.…”
mentioning
confidence: 99%
“…It may be that modifying their sports reduced the likelihood of further injury and possibly the development of osteoarthritis, which may be higher in patients with reconstruction who are involved in higher-level activities. 14 This very important question will be addressed in a longer-term study.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 45 evaluated postural stability in ACLR patients and found prolonged T1rho in asymmetric patients persisted up to 2 years where the asymmetric group also reported worse KOOS in all subscores than symmetric ACLR patients and controls. Finally, Friedman et al 46 showed that those achieving a Marx Activity Score of 11 or above at 3 years showed significantly greater T1rho elevations consistent with increasing degeneration over the same time frame. In addition, higher Knee Osteoarthritis and Injury Outcomes Score (KOOS) Quality of Life (QOL) scores correlated with more significant cartilage degeneration.…”
Section: Compositional Mri Allows For Noninvasive Early Assessment Of Articular Cartilage Statusmentioning
confidence: 98%